New G 2-invariant supersymmetric AdS4 vacua in 11d supergravity and holography - Xuao Zhang (Journal of High Energy Physics)
Abstract We study the most general G 2-invariant AdS4 vacua in 11 dimensional supergravity preserving 4 real supercharges, with the goal of understanding the IR fixed points of the RG flow induced by the cubic deformation of the ABJM theory. We identify a new G 2-invariant background, which completes the web of RG flows connecting its holographic dual with the ABJM theory and the (cubic analogue of) mass-deformed ABJM theory with SU(3) × U(1) isometry. Our holographic study gives non-trivial predictions for the strongly-coupled field theory dual.